Genoprotective and Antioxidant Effects of Olea ferruginea Leaf Extract Through Micronucleus and Antioxidant Assays - Abid Ullah; Shah, Zafar Ali; Khan, Muhammad Ismail; Kifayat Ullah; Muhammad Khisroon (Indus Journal of Bioscience Research, 2025)
Olea ferruginea has plenty of phenolic compounds with significant antioxidant potential, but its genoprotective effects against chemotherapeutic drug–induced DNA damage remains unexplored. This study demonstrates the genoprotective and antioxidant activities of Olea ferruginea leaf extract against cisplatin-induced genotoxicity in rats, which is supported by its in vitro free radical scavenging experiment. Sprague-Dawley rats were used as a negative control, a positive control (cisplatin only 2 mg/kg), and extract treated groups (cisplatin + Olea ferruginea extract). The extract treated groups received doses of 25, 50 and 75 mg/kg for 7, 14 and 21 days. The bone marrow genotoxicity was evaluated through a micronucleus experiment, whereas the antioxidant potential was confirmed by using DPPH and H₂O₂ radical scavenging analysis with the extract concentration of 25, 50,100,200 and 500 μg/mL. The obtained results demonstrate that in the positive control group, cisplatin significantly enhanced micronuclei frequency (7.3 ± 2.2 on day 21) as compared to negative controls (1.3 ± 1.2) and the treated group (2.2 ± 0.7). In addition, the micronucleus formation was reduced by treating with Olea ferruginea in a dose and time dependent manner. The reduction in micronuclei occurred with the high dose of 75 mg/kg, which resulted in a frequency of 2.2 ± 0.7 on day 21 (p < 0.0001). In, in vitro, the extract demonstrated concentration-dependent radical scavenging potential with 60.95% for DPPH at 500 μg/mL and 39.79% for H₂O₂ with 500 μg/mL and 59.69 % with 200 μg/mL concentration. These results highlight its performance as a natural chemoprotective and genoprotective candidate and permit supplementary bioactive compound isolation and its mechanistic studies.